First aid self: first aid home remedies mobile app / Rattana Abdul Rahim - Abdul Rahim, Rattana (2022)
The project aims to develop an informative mobile application for first aid and home remedies to assist people in emergency situation at home. With First Aid Self, it will assist the user in proper and safe first-aid action and the use of home remedies. The objectives of this project are to identify the user requirements, to design and to develop First Aid Self: First Aid Home Remedies Mobile App. The scope for the informational content is focus only for the non-severe injuries, and the platform used is Android. This project used Mobile Application Development Life Cycle (MADLC) until testing phase as a methodology approach to develop this app. The features of this mobile apps are user profile, informational content of home remedies, series of first aid videos, add notes for the home remedies where user can save the notes for their own use or share it to others. Next, the chat room. The users can exchange their knowledge and information about first aid and home remedies to assist one another. This project will make use of the Android platform, as well as the English language. The people in Shah Alam are the intended target user of this First Aid Self mobile app. According to the results of user testing, all the functionalities of the First Aid Self mobile application work as anticipated. According to the testers, the application is easy to navigate, and all information and symbols are properly organised. The testers really liked the colour palette and icons used in this mobile application. Furthermore, all the testers agreed that this smartphone application has all of the necessary components and would genuinely assist them in studying first aid and home remedies. Numerous home remedies used all around the world will be included to the First Aid Self mobile app as future recommendations to further expand it. The therapies will also cover the entire sickness, not only for non-severe conditions.